Coagulation phenotype of wild-type mice on different genetic backgrounds. (February 2019) - Kopić, Alexandra; Benamara, Karima; Schuster, Maria; Leidenmühler, Peter; Bauer, Alexander; Glantschnig, Helmut; Höllriegl, Werner
Genetically engineered mouse models are used to investigate beneficial treatment in haemophilia by comparison with wild-type mice. It has been recognized that wild-type and haemophilic mice of different genetic backgrounds show different bleeding phenotypes. We assessed ex-vivo coagulation parameters in nine wild-type substrains of 129S1/Sv, BALB/c and C57BL/6 mice applying thromboelastography (TEG), activated partial thromboplastin time (aPTT), prothrombin time (PT) and fibrinogen levels. The comprehensive ex-vivo data are discussed in view of results from a tail-tip bleeding assay. Time to first clot formation ( R -time) showed higher within-substrain (CV range: 28–54%) and higher between-substrain (median range: 25.53–42.60 min) variation for BALB/c than for C57BL/6 mice (CV range: 14–31%; median range: 22.45–24.93 min). Median R-time for 129S1/Sv mice was 30.42 min (CV: 33%). No distinct strain differences were observed for maximum amplitude (MA), aPTT, or PT, but males generally showed higher MA and shorter aPTT than females. Males of all substrains had higher fibrinogen levels than females. The heightened in-vivo variability (CV range: 81–171%; median range: 36.00–469.50 mg) in the tail-tip bleeding assay and increased blood loss in wild-type C57BL/6 male mice was not reflected in ex-vivo coagulation parameters. In general, ex-vivo coagulation results appeared consistent within substrains, but showed substrain and sex differences of variable magnitudes. We conclude that alignment of the mouse substrain genetic background to the experimental model is critical to reduce data variability and animal numbers.